Skin Metastasis with Non-healing Ulcer: An Unusual Presentation of Metastasis of Carcinoma Cervix - Sayeeda, Nur; Rahman, Shamima; Nahar, Shamsun; Afroj, Sultana (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Carcinoma of the uterine cervix is the most common gynecological malignancy in developing countries. Most frequent metastasis of carcinoma cervix occurred locally. Distal metastasis via lungs, bones, liver reported frequently but skin metastasis are very rare incidence. Here we present a case of skin metastasis of carcinoma cervix. A 42 year old lady presented with a skin swelling with non-healing ulcer over the swelling in outpatient department of Dhaka Medical College. She had history of Wertheim’s Hysterectomy 1year back for carcinoma cervix stage II A (FIGO classification). On skin biopsy she was diagnosed as a case of cutaneous metastasis of carcinoma cervix. J Bangladesh Coll Phys Surg 2019; 37(2): 89-92